THE PERILS OF BUREAUCRATIC INERTIA: A STEPS TOWARD ENHANCING GOVERNMENT MANAGEMENT - Fathani, Aqil Teguh; Putera, Roni Ekha; Mohamed, Nabila (Universitas Riau Kepulauan, 2024)
Abstrack : The aims of study is to investigate phenomenon of bureaucratic inertia within the Indonesian government system, which detrimentally affects government governance, administrative systems, and public services provided to the people. It is crucial to acknowledge the significant risk posed by the persistence of bureaucratic inertia in the absence of any proactive measures to address and advance necessary changes. This research employs a comprehensive literature review, incorporating 35 relevant scholarly sources that are closely aligned with the current study. The occurrence of bureaucratic inertia in Indonesia is a significant challenge since local institutions always face pressure from the central government, resulting in diminished authority, influence, and power. From an institutional standpoint, it is crucial to have transparency mechanisms in place to guide decision-makers. These mechanisms should allow for the authorization or restriction of actions, enforceable regulations and procedures, and appropriate incentives or penalties to ensure wise decision-making. By implementing such measures, institutions can gradually develop into responsible entities that prioritize transparency in meeting public demands. From a capacity standpoint, the key criteria for overcoming bureaucratic inertia include improving the organizational and managerial structure, facilities, and infrastructure, and promoting the establishment of an extensive network. Furthermore, there exists a significant prospect to engage in cooperation with exterior stakeholders to leverage solutions to compete with regions that possess greater advancement than others. Keywords : government; governance; bureaucratic inertia; government management; decentralization; Indonesia.